Long-Term Outcome of Horses Undergoing Unilateral Mandibular Condylectomy and Meniscectomy for Temporomandibular Joint Disease - White, Sarah A.; Canada, Nathan C.; Carmalt, James L.; Schumacher, James; Amitrano, Fernando N.; Ortved, Kyla; Henry, Travis J.; Brounts, Sabrina H.; Arnold, Carolyn E. (Frontiers in Veterinary Science, 2022)
Background There are no reports describing the long-term outcome of sport horses undergoing unilateral mandibular condylectomy with meniscectomy (UMC) for treatment for severe temporomandibular joint (TMJ) disease (TMD). Whether horses undergoing UMC require a specialized diet, can return to riding with a bit, or return to intended function after surgery is unknown. Objective To determine the long-term outcome of horses undergoing UMC for treatment of severe TMD. Study Design A multi-institutional, retrospective study. Methods Medical records obtained from seven equine referral hospitals of horses with severe TMD that underwent UMC were reviewed. Details regarding the presenting complaints, results of clinical examination, findings of diagnostic imaging, surgical technique, and outcome (including long-term follow-up with an owner questionnaire) were recorded. Results Eleven horses fit the inclusion criteria. Three had severe idiopathic osteoarthritis, and eight had confirmed septic osteoarthritis of the TMJ. The most common post-operative complications were drainage and peri-incisional swelling (n = 5). One horse developed a hematoma at the surgical site because the facial artery was inadvertently transected during the approach, causing the condylectomy to be postponed. All horses were discharged alive from the hospital, and 10 returned to their previous or intended use. All had complete resolution of clinical signs of TMD. One mare was retired from athletic use due to her genetic value as a broodmare. One horse was euthanized 2 years after UMC due to progressively worsening of clinical signs of temporohyoid osteoarthropathy (THO), which were not present before surgery. When available, owner satisfaction of the results of the procedure was excellent. Main Limitations Sample size; multiple institutions; owner bias. Conclusions Unilateral mandibular condylectomy should not be considered a salvage procedure. Horses treated for severe TMD by UMC can return to their previous or intended level of athletic performance and do not require a specialized diet.